Serum vitamin B12 concentrations in children - Zamani, Vahide; Özsoylu, Şinasi; Sakallı, Funda; Laleli, Yahya (The Turkish Journal of Pediatrics, 1986)
Vitamin B12 levels of 40 healthy children were determined by using the “radioimmunoassay kit” method. They were found to range from 200 to 1250 pg/ml with a mean of 558.8 ± 268 pg/ml.It was found markedly low (< 100 pg/ml) in two patients only, and these had megaloblastic anemia of vitamin B12 deficiency.Very high vitamin B12 levels (> 2000 pg/ml) were found in three patients with chronic myeloid leukemia and in a case of preleukemia. A very high level (> 2000 pg/ml) was also found in a case of hemophilia during massive bleeding in the hip joint, but not in the other hemophilic cases.
Keywords: children; hematologic disorders; vitamin B12